Recent advances in materials for hemostatic management. (21st October 2021) - Liu, Lu; Hu, Enling; Yu, Kun; Xie, Ruiqi; Lu, Fei; Lu, Bitao; Bao, Rong; Li, Qing; Dai, Fangyin; Lan, Guangqian
Abstract : Traumatic hemorrhage can be a fatal event, particularly when large quantities of blood are lost in a short time. For different wound types (superficial wound, deep wound…), dozens of hemostatic materials came into being. Abstract : Traumatic hemorrhage can be a fatal event, particularly when large quantities of blood are lost in a short period of time. Therefore, hemostasis has become a crucial part of emergency treatment. For small wounds, hemostasis can be achieved intrinsically depending on the body's own blood coagulation mechanism; however, for large-area wounds, particularly battlefield and complex wounds, materials delivering rapid and effective hemostasis are required. In parallel with the constant progress in science, technology, and society, advances in hemostatic materials have also undergone various iterations by integrating new ideas with old concepts. There are various natural and synthetic hemostatic materials, including hemostatic powders, adhesives, hydrogels, and tourniquets, for the treatment of severe external trauma. This review covers the differences among the currently available hemostatic materials and comprehensively describes the hemostatic effects of different materials based on the underlying mechanisms. Finally, solutions for current issues related to trauma bleeding are discussed, and the prospects of hemostatic materials are proposed.